Essays on firms and globalisation - Bajgar, M (2015)
This dissertation consists of three stand-alone substantive chapters. It examines how various aspects of globalisation – openness to international trade, inflows of foreign direct investment and exposure to foreign demand shocks – affect economic performance through their impact on individual firms. The first substantive chapter presents a theoretical model of international trade with heterogeneous firms that differ not only by their productivity but also by the distortions they face. For a particular distribution of productivity and distortions, it shows that the distortions which affect the domestic and export sales in the same way and are correlated with productivity reduce the welfare gains from trade, while the distortions affecting only domestic sales tend to increase them. In addition, it documents that correlated distortions lead to a bias in an influential recent method for estimating the gains from trade. The following chapter empirically examines the link between the presence of multinational companies and the export sophistication of domestic firms in an emerging economy. The analysis is based on the matched firm and customs panel data from Romania covering the period 2005-11. The results show a positive relationship between the unit values of goods exported and imported by Romanian firms and the multinational companies' presence in downstream (input sourcing) industries. These results are consistent with quality upgrading being an additional channel through which local suppliers benefit from contacts with their multinational customers. The last chapter examines how Romanian manufacturing firms reacted to a dramatic drop in the export demand during the global trade collapse of 2008 and 2009. The exogenous effect of a fall in exports is identified by instrumenting exports with a firm-specific index of foreign demand. The results indicate that exporting firms were unable to redirect their sales to the domestic market and were forced to abruptly reduce their employment, material expenditure and investment, passing the shock to their suppliers. The results suggest that the export status of a firm may be a poor predictor of its vulnerability to a negative foreign demand shock.